BEHAVIOUR OF TWELVE SPHERICAL CODES IN CW EPR POWDER SIMULATIONS. UNIFORMITY AND EPR PROPERTIES - CRĂCIUN, Cora (Studia Universitatis Babeș-Bolyai Chemia, 2016)
This paper assesses the efficiency of twelve spherical codes in CW EPR powder simulations. The spherical codes are either regular or are generated using optimisation methods. The EPR simulations are performed for spin systems with axial and rhombic symmetry. The spherical codes are compared using Voronoi tessellation-based homogeneity and EPR properties.